2007
DOI: 10.1029/2005jd006741
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the inorganic and organic composition of size‐segregated aerosol in Rondônia, Brazil, from the biomass‐burning period to the onset of the wet season

Abstract: [1] The aerosol characterization experiment performed within the Large-Scale BiosphereAtmosphere Experiment in Amazonia-Smoke, Aerosols, Clouds, Rainfall and Climate (LBA-SMOCC) field experiment carried out in Rondônia, Brazil, in the period from September to November 2002 provides a unique data set of size-resolved chemical composition of boundary layer aerosol over the Amazon Basin from the intense biomassburning period to the onset of the wet season. Three main periods were clearly distinguished on the basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
160
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 160 publications
(188 citation statements)
references
References 63 publications
25
160
0
3
Order By: Relevance
“…They are completely water-soluble and thus contribute to WSOC in aerosol. Sugar compounds are generally found to be more abundant in coarse fraction than the fine one (Fuzzi et al, 2007;Yttri et al, 2007), supporting that they are likely derived from primary biological aerosol particles. Graham et al (2003) reported that fructose, sucrose and glucose showed higher daytime concentrations, which were explained by the specific daytime release of pollen, fern spores and other "giant" bioaerosols.…”
Section: Diurnal Variations Of Primary Saccharidesmentioning
confidence: 75%
“…They are completely water-soluble and thus contribute to WSOC in aerosol. Sugar compounds are generally found to be more abundant in coarse fraction than the fine one (Fuzzi et al, 2007;Yttri et al, 2007), supporting that they are likely derived from primary biological aerosol particles. Graham et al (2003) reported that fructose, sucrose and glucose showed higher daytime concentrations, which were explained by the specific daytime release of pollen, fern spores and other "giant" bioaerosols.…”
Section: Diurnal Variations Of Primary Saccharidesmentioning
confidence: 75%
“…Potential chemical interference due to Apiezon on the SFU filters can be excluded because sulfur was also measured by PIXE from samples collected with an SDI impactor (cf. Fuzzi et al 2007). Sulfur values from Apiezon-coated SFU filters and impactor filters agreed within 10%.…”
Section: Influence Of Meteorology and Chemistrymentioning
confidence: 76%
“…Various conventional filter-based samplers were deployed simultaneously including a denuder-filter pack (DFP: Teflon and impregnated Whatman filters), a stacked-filter unit (SFU: polycarbonate filters) and a High Volume dichotomous sampler (HiVol: quartz-fiber filters). Gas-to-particle conversion processes and aerosol chemistry at this tropical site have been investigated in previous studies (e.g., Falkovich et al 2004;Fuzzi et al 2007;Hoffer et al 2006;Mayol-Bracero et al 2002;Trebs et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The SOA and biomass burning particles are main contributors to WSOC and both are known to be preferentially associated with the PM 2.5 size fraction (e.g. Fuzzi et al, 2007). From a seasonal standpoint, at Aveiro, the WSOM contributes to 13e32% of the PM mass during winter, whereas its contribution diminishes during summer to 5.7e10%.…”
Section: Contribution Of Wsoc To Pm Massmentioning
confidence: 99%